The Effects of Multiple Sexual Partners and Condoms Use on the Incidence of HIV in Men Having Sex with Men - Evi Erlinda Wati; Rahayu Lubis; R. Kintoko Rochadi (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: HIV has become a problem in the international community. Rapid transmission of HIV becomes a threatfor the entire global community in order to prevent an increasingly widespread. One of the factors that causes HIV is unhealthy sexual behavior. This study aimed to determine the effect of changing partners and condom use on HIV incidence in men having sex with Men (MSM) in the Teladan Health Center in Medan.Subjects and Method: This was case-control study conducted at Teladan Health Center, in May 2018. A sample of 96 study subjects was selected for this study. The dependent variable was the incidence of HIV. The independent variables were multiple sex partners and condom use. HIV status was obtained from medical record. The other variables were measured by questionnaire. The data were analyzed by a multiple logistic regression.Results: Multiple sexual partners (OR= 2.93; 95% CI= 1.25 to 6.86; p= 0.022) and absence of condom use (OR= 2.83; 95% CI= 1.23 to 6.52; p= 0.024) increased the risk of HIV among men having sex with men.Conclusions: The occurrence of HIV in MSM is probably 2.9 times due changing partner actions and 2.8 times due to the inconsistent condom use.Keywords: HIV, multiple, sexual partners, condom use, men having sex with menCorrespondence: